Integrating Zooarchaeology and Paleoethnobotany: A Consideration of Issues, Methods, and Cases - Butler, Virginia L. (Ethnobiology Letters, 2010)
Review of Integrating Zooarchaeology and Paleoethnobotany: A Consideration of Issues, Methods, and Cases. Amber M. VanDerwarker and Tanya M. Peres, eds. 2010. Springer, New York. Pp. 317, 13 color illustrations, 13 black-and-white illustrations. 129.00 (hardback). ISBN 9781441909343.